A EXPERIÊNCIA COMO ACADÊMICO -MONITOR DE FUNDAMENTOS DE ENFERMAGEM - Miguel, Diogo B. d.; Kusiack, Adriana; Carli, Larissa d.; Paganelli, Maiara C.; Girardon-Perlini, Nara M. O. (Salão do Conhecimento, 2013)
Resumo